A pharmacoeconomic study on Jan Aushadhi generics versus branded pharmaceutical formulations in India - Anandhasayanam, A; Kannan, S; Rajamurugan, R (Indian Journal of Community Health, 2024)
Background: Healthcare costs are a major burden on the society of developing countries like India. Countries like India try to limit healthcare costs in support of generic medicine. So, the Indian government initiated the Jan Aushadhi scheme in 2008 to provide high-quality generic medication at a low cost. Aim: The aim of the study was to compare the cost difference between Jan Aushadhi generic pharmaceutical formulations and branded medications in Tamil Nadu. Settings and Design: Pharmaco economic - Cost minimization observational study. Methods and Material: Study Duration: Five months, from February 2023 to June 2023. Study Place: 10 Jan Aushadhi outlets from various districts of Tamil Nadu. Sampling technique: Convenience sampling technique Statistical analysis used: Mean median, mode and Percentage. Results: A total of 729 medications were available in 10 Jan Aushadhi outlets. The Jan Aushadhi outlet has the most cardiovascular medications and the fewest antimalarial medications among different categories of drugs. Erythropoietin has the biggest cost difference between the average cost of branded medications and Jan Aushadhi drug costs, while Digoxin has the lowest cost difference. Antitubercular drugs, Oxytocics, Antileprosy drugs, Antiparkinsonism categories of drugs also delisted in Jan Aushadhi outlet. Conclusions: Compared to branded drugs, Jan Aushadhi's generic drugs are 64.65 % less costly on an average as observed in our study. The manufacturer of Jan Aushadhi shops is a WHO and GMO-certified company, and they manufacture branded drugs. So, there will be no quality compromise in Jan Aushadhi’s generic drugs.